2011
DOI: 10.1016/s0028-3843(14)60057-8
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic deep brain stimulation for the treatment of Parkinson disease

Abstract: Cardinal symptoms of Parkinson's disease can be safely and effectively treated with STN DBS in selected group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
9
0
6
Order By: Relevance
“…the Stn is currently the preferred target structure used for DBS treatment in patients with advanced PD [17,18]. Besides, different groups have reported that the stimulation of the Zi is an alternative target for DBS [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…the Stn is currently the preferred target structure used for DBS treatment in patients with advanced PD [17,18]. Besides, different groups have reported that the stimulation of the Zi is an alternative target for DBS [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The subthalamKerl HU et al . Zona incerta at 7 Tesla ic nucleus (STN) represents the commonly chosen target site to suppress resting tremor in patients with PD [1,5,6] . Despite the improvements in motor function, several clinical trails have yielded information about negative limbic effects of STN DBS, including depression, apathy, and decreased cognitive function [7,8] .…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…Polish reports on deep brain stimulation fail to include any mention of the treatment of SD in any patient suffering from generalized dystonia. Polish publications on GPi stimulation in the management of dystonia confirm that the method has been both effective and safe for the treatment of diverse motor disorders including advanced Parkinson disease over the past several years [33][34][35].…”
Section: Deep Brain Stimulation In the Treatment Of Status Dystonicusmentioning
confidence: 96%